The Syntax and Semantics of Converbs in Modern Slavic Languages - Nikolin-Dukai, Lilla (SlavVaria, 2024)
The paper investigates the category of converbs in modern Slavic languages, a grammatical category exhibiting ongoing development. Converbs’ morphological, syntactic, and semantic properties are examined across various Slavic languages. By comparing their syntax, usage, and semantics, the study aims to identify connections between the current state of converbs and the typological features of each language. Contrary to the initial hypothesis, the analysis reveals that modern Slavic languages exhibit significant variation in the syntax and semantics of converbs, highlighting the ongoing evolution of this grammatical category within the Slavic language family.